Privacy by design for the Internet of things : building accountability and security - Crabtree, Andrew; Haddadi, Hamed; Mortier, Richard (IET security series ;, 2021)
In this edited book, the authors delineate the challenges of building accountability into the Internet of Things and solutions for delivering on this critical societal challenge. They explain how the accountability principle impacts IoT development by presenting empirical studies of accountability in action.